2006
DOI: 10.1590/s1516-89132006000500011
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the seasonal and environmental patterns and host reproduction on the metazoan parasites of Prochilodus lineatus

Abstract: One hundred and forty-eight specimens of Prochilodus lineatus (Valenciennes, 1836)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 16 publications
(14 reference statements)
2
16
0
1
Order By: Relevance
“…LIZAMA et al (2006) showed that the abundance of S. nanii in P. lineatus was higher during the rainy season the same is valid during the dry season for S. nanii in P. argenteus. Abiotic factors can interfere directly and/or indirectly in the development of parasites (POULIN 1996).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…LIZAMA et al (2006) showed that the abundance of S. nanii in P. lineatus was higher during the rainy season the same is valid during the dry season for S. nanii in P. argenteus. Abiotic factors can interfere directly and/or indirectly in the development of parasites (POULIN 1996).…”
Section: Discussionsupporting
confidence: 52%
“…DYER et al (1999 described Saccocoelioides agnostomun Dyer, Bunkley-Williams & Williams Jr, 1999 and provided a summary of the genus Saccocoelioides. LIZAMA et al (2006) analyzed the influence of seasonal and environmental patterns and host reproduction on S. nanii and other metazoan parasites of Prochilodus lineatus (Valenciennes, 1836). They showed that the abundance of the latter was higher during the reproductive period of the host, and that the prevalence was positively correlated with water temperature.…”
Section: Species Of Saccocoelioidesmentioning
confidence: 99%
“…The difference in abundance between the two studies (current data and Paraguassú et al (2002)) is reflected in the short sampling period in the present study, which focused on the summer. According to Costa et al (1997), the spawning period for red porgy caught in the Cabo Frio region extends from November to January which would explain the differences in prevalence and abundance that coincide with the peak reproductive period of the host, since during this period the fish are more susceptible to parasitism caused, among other factors, by the stress of reproduction (LIZAMA et al, 2006). At this same time of year, there is the effect of the South Atlantic Central Water (SACW) phenomenon, which means that rearing takes place in a nutrient-rich mass, thus resulting in increased food availability throughout the food chain.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have observed that the reproductive migration pattern of a host can be a determining factor in the composition and structure of parasite communities, as the short and long migrations performed by this species over its lifetime permit the fish to exploit diverse environments, increasing the possibility of infection/infestation by diverse species of parasites (Lizama et al 2006). Consequently, these divergent migratory characteristics may affect the endoparasite fauna, as related species usually exhibit divergent characteristics that make the coexistence possible (Dogiel 1961;Balassa et al 2004).…”
Section: Fauna Endoparasitária Dementioning
confidence: 99%